The identity of Artemisia brevis (Asteraceae, Anthemideae) from Xinjiang, China - Guo, Xin-Qiang; Wang, Long; Yang, Qin-Er (Phytotaxa, 2022)
Critical observations on herbarium specimens (including type material) and living plants in the wild indicate that Artemisia brevis (= A. argyrophylla var. brevis) (Asteraceae, Anthemideae), described from Xinjiang in China, differs remarkably from A. argyrophylla but is not essentially different from A. rupestris, an easily recognizable species quite common in Xinjiang. We therefore place A. brevis and A. argyrophylla var. brevis in synonymy with A. rupestris.